Adaptive Dynamic Programming-based Tracking Controls of Multi-Motor Driven Systems - LYU Yongfeng; JIAN Long (Taiyuan Ligong Daxue xuebao)
[Purposes] The unknown multi-motor driven load systems are addressed in this paper with game theory and adaptive dynamic programming. [Methods] The neural network (NN) is used to approximate the unknown dynamics. On the basis of the approximated dynamics, the optimal performance index is defined and the optimal tracking controls are designed. The adaptive dynamic programming based tracking controls can be divided into steady-state controls and optimal feedback controls. Steady-state controls can be directly obtained with the tracking commands and load dynamics. The optimal feedback controls are obtained with an approximate dynamic programming algorithm, which can be used to research the saddle point and minimized the performance index. The convergence of the NN weights is analyzed and the stability of the load system is proved. [Findings] A simulation is provided to illustrate the effectiveness of the methods, which can optimize the load performance.